PENERAPAN SISTEM PENGENDALIAN INTERN ATAS PEMBIAYAAN KONSUMEN DALAM PENYALURAN KREDIT PEMILIKAN RUMAH (KPR) PT BANK SYARIAH MANDIRI CABANG SAMARINDA - Dewi, Anita Puspita (EKONOMIA, 2019)
The purpose of this study is to improve and streamline Islamic banking products so that the achievement of the objectives of the consumer financing system in providing housing loans must be implemented by the company as a precautionary measure of the problems obtained from the housing finance credit system, evaluating Ownership Credit Systems and Procedures House (KPR) applied by PT Bank Syariah Mandiri Samarinda Branch. The application is compared to the Bank Indonesia Regulations that have been determined. This is done in order to see that with the conformity of procedures with Bank Indonesia regulations, the level of credit distribution can be controlled. These procedures are described to determine the factors that cause bad credit.The theoretical basis used is the Accounting Information System which focuses on the Standard Operating Procedure for Administration of Home Ownership CreditResearch results show that the Standard Operating Procedure for Home Ownership Credit (KPR) is in accordance with Bank Indonesia Circular Number 12/38 / DPNP dated December 31, 2010 Concerning the Guidelines for Preparing the Administration of Standard Operating Procedures for Home Ownership Loans in the Framework of Sekurutisasi. Then based on the results of interviews and observations of the implementation of the procedures it can be concluded that the procedures and control of the occurrence of credit disbursement at the Bank Mandri Syariah Branch Samarinda have been sufficiently implemented properly and correctly in accordance with the applicable Standard Operating Procedure (SOP), the principle of concerns, and Bank Indonesia regulations regarding credit provision. Each officer concerned, has understood the duties and obligations of each and carried out responsibly and guided the applicable rules.